Children’s literacy skills development through non-formal education: a scoping review - Pek, Lim Seong; Khusni, Hafizah Kusnek; Yob, Fatin Syamilah Che; Zaid, Najimi Najiha Mohd; Ne'matullah, Khairul Firdaus; Mee, Rita Wong Mee; Azli, Nur Syafiqah Saiful (Intelektual Pustaka Media Utama, 2024)
The rapid advancement of technology in recent years has brought about profound changes in every aspect of our lives. Such technological advancement has impacted children in a digital age where technology permeates every facet of their existence, from education to entertainment and communication to socialization. The younger generations today appear deficient in motor, emotional, and social abilities. They appear to exhibit higher levels of aggression, anxiety, dependency, and reduced creativity. Integrating non-formal education into children’s learning aims to maximize enjoyment and engagement by capturing children’s interest and inspiring them to continue learning. Thus, non-formal education encompasses a spectrum of curricular activities in the natural environment outside of the school area. This scoping review aims to identify the focus skills development among primary school learners and how non-formal educational activities could boost learners’ learning ability. Four databases, including Scopus, web of science (WoS), Education Resources Information Center (ERIC), and ScienceDirect, were used in this research, which found 36 articles for eligibility. Only 15 articles are eligible for analysis and reference after the exclusion and inclusion process for data collection. The findings show that non-formal education offers learners the opportunity to explore a multitude of interests beyond the structured confines of the classroom.